Analisa Pengaruh Antara Rencana Belajar, Locus of Control Terhadap Prestasi Belajar SMA BSM 1 Tahun 2024 - Andry Roy (Departement of Mathematics Education, 2024)
all learning objects at the high school level must be taken into consideration. Efforts are made to carry out theoretical and practical studies in a balanced manner. Investigation and understanding at the theoretical and practical levels provide an understanding of the various material in all subjects provided by the school to students. The increase in student abilities demonstrated through learning outcomes can definitely be used to adapt and innovate to meet economic, environmental and social needs in an ever-developing world. This includes addressing the global challenges of climate change and energy constraints by designing processes to maximize the efficient use of the Earth's limited resources. Some lessons are practical learning. Students are trained to conduct simple qualitative and quantitative research both individually and collaboratively regarding various real-world phenomena. Students learn to find problems, create hypotheses, design simple experiments, conduct experiments, analyze data, draw conclusions and communicate experimental results both in writing and orally.